Unwed Mother By Choice: A Study In The Context Of Law And Society - Payashwini sharma, Dr. Aqueeda khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
One of the objectives of this study was to develop an intervention model for working with these young unwed mothers. While dealing with unwed mothers it should be kept in mind that each individual is unique and the intervention should not be a blanket approach. There is an urgent need of trained professionals to provide quality interventions.It is in context that the Researcher gave an orientation programme for the Social workers and functionaries of the licensed homes with the objective of enhancing their knowledge, attitude and skills while working with these marginalized and deprived groups of unwed mothers. The implications of the findings for future research and program development were discussed.